Klimatfaktorers inverkan på granbarkborrens svärmningsintensitet i Medelpad - Hamberg, Marica (2015)
The spruce bark beetle (Ips typographhus) is one of the 25 000 species of insects in Sweden, an insect of great economic importance because it can alone terminate forest of high value. During the past decade, insights of climate change received with increasing attention. If the future brings a milder climate in the north and therefore a longer growing season, one would think that it would only affect the forestry to the better? Yet in recent time, outbreaks after storm felling seems to occur more frequently. The Spruce bark beetle ruins millions of cubic meter of Norway spruce (Picea abies) in Sweden alone, with more frequent storm felling and a larger amount of wind thrown threes in the forests there will also be room for an advancing reproduction. The aim of this study is to investigate the importance of how spruce bark beetle get affected by climate factors and which climate who have the greatest impact on their flight period. The year 2009, forest owners in Medelpad County started to come across several groups of standing dead Norway spruce in the forest. When SCA and the Swedish Forestry Agency made an inventory 2010, they both could determent that it was the spruce bark beetle that caused it. The study has obtained data from the Swedish Forestry Agency during the period 2011-2013, the area trap catches are collected on are Kovland in Medelpad and the weather observations are received from the Swedish Meteorological and Hydrological Institute. The correlations reported seasonal climate in terms of average temperature and precipitation versus trap catches. The study will not examine the biotic factors affecting bark beetle reproductive success.